2020
DOI: 10.1080/13696998.2020.1722678
|View full text |Cite
|
Sign up to set email alerts
|

Oral semaglutide versus injectable glucagon-like peptide-1 receptor agonists: a cost of control analysis

Abstract: Aims:The efficacy and safety of oral semaglutide, the first glucagon-like peptide-1 (GLP-1) receptor agonist developed for oral administration for the treatment of type 2 diabetes, was evaluated in the PIONEER clinical trial program, and a recently published network meta-analysis allowed comparison with further injectable GLP-1 receptor agonists. The present study aimed to assess the short-term costeffectiveness of oral semaglutide 14 mg versus subcutaneous once-weekly dulaglutide 1.5 mg, onceweekly exenatide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 34 publications
0
19
0
3
Order By: Relevance
“…Furthermore, a long-term cost-effectiveness analysis demonstrated that oral semaglutide was more cost effective than empagliflozin, sitagliptin, and liraglutide for patients with T2D in the United Kingdom ( Bain et al, 2020 ). Hansen et al (2020) identified that when two glycaemic lowering goals, HbA1c ≤ 6.5% and HbA1c < 7.0%, are reached, the cost of other subcutaneous injections of GLP-1 receptor agonists is higher than that of semaglutide. Johansen et al (2020) indicated that compared with once-daily liraglutide 1.2 mg, the life expectancy with once-weekly semaglutide 1 mg increased by 0.21 years, and the quality-adjusted life expectancy increased by 0.3 years.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a long-term cost-effectiveness analysis demonstrated that oral semaglutide was more cost effective than empagliflozin, sitagliptin, and liraglutide for patients with T2D in the United Kingdom ( Bain et al, 2020 ). Hansen et al (2020) identified that when two glycaemic lowering goals, HbA1c ≤ 6.5% and HbA1c < 7.0%, are reached, the cost of other subcutaneous injections of GLP-1 receptor agonists is higher than that of semaglutide. Johansen et al (2020) indicated that compared with once-daily liraglutide 1.2 mg, the life expectancy with once-weekly semaglutide 1 mg increased by 0.21 years, and the quality-adjusted life expectancy increased by 0.3 years.…”
Section: Discussionmentioning
confidence: 99%
“…The relative cost-effectiveness of the two semaglutide formulations has not been directly compared. However, both subcutaneous and oral semaglutide have been reported to be more costeffective and offer lower cost-of-control compared with other injectable GLP-1RAs and oral glucose-lowering drugs, although this may vary between different patient cohorts and healthcare settings (58)(59)(60)(61)(62)(63)(64). In addition, switching may be dependent on non-medical decisions outwith the physician's choice, with a recent expert consensus indicating that non-medical triggers for switching to subcutaneous semaglutide from other GLP-1RAs also included formulary changes and insurance mandates, as well as cost considerations (65).…”
Section: Selection Of the Most Appropriate Formulationmentioning
confidence: 99%
“…In a cost of control analysis by Hansen et al for the US market, orally administered semaglutide was found to be cost effective in comparison to dulaglutide, exenatide, liraglutide and lixisenatide. Cost of a 14 mg dose of orally administered semaglutide came out the least at USD 15,430 and USD 17,383 for patients achieving glycaemic targets of < 7% and ≤ 6.5%, respectively [ 46 ]. In another cost-effectiveness analysis done for the UK market, orally administered semaglutide 14 mg was found to be cost effective relative to sitagliptin 100 mg and empagliflozin 25 mg and dominant in comparison to liraglutide 1.8 mg daily dose for the treatment of T2DM.…”
Section: Cost Of Oral Vs Injectable and Other Therapiesmentioning
confidence: 99%